Protective role of aqueous Coriandrum sativum seed extract in diet-induced glucolipid metabolic disorder through gut–liver axis regulation - Xu, Yuru; Cao, Ying; Zou, Linen; Wulanna,; Liu, Xinyu; Yan, Shutong; Liu, Chengyi; Gao, Mengran; Zhan, Jingke; Wang, Qingchun; Wu, Chongming (Frontiers in Endocrinology, 2026)
ObjectiveTo elucidate the protective effects of aqueous Coriandrum sativum seed extract against high-fat, high-sugar diet (HSFD)-induced glucolipid metabolic disorder in mice, with particular focus on gut–liver axis regulation involving hepatic metabolism, oxidative stress, inflammation, and gut microbiota composition.MethodsMale mice were fed an HSFD and orally treated with Coriandrum sativum seed extract (1.0 or 2.0 g/kg/day) for eight weeks. Biochemical parameters, histopathology, hepatic gene expression, oxidative stress markers, and gut microbial profiles were assessed via standard assays, RT-qPCR, Western blot, histological staining, and full-length 16S rRNA gene sequencing with functional prediction.ResultsThe extract significantly ameliorated HSFD-induced metabolic impairments, including hyperglycemia, hyperlipidemia, insulin resistance, and hepatic steatosis. Histological improvements were observed in the liver, pancreas, and colon. Hepatic expression of FAS, NF-κB, and IL-6 was suppressed, while PPARα and LDLR expression was restored. Antioxidant defenses were enhanced by reducing malondialdehyde and increasing superoxide dismutase activity. Microbiota analysis revealed partial restoration of beneficial taxa such as Lactobacillus murinus and Lachnospiraceae_UCG-006, alongside enrichment of microbial pathways related to energy and carbohydrate metabolism.ConclusionAqueous Coriandrum sativum seed extract exerts systemic metabolic benefits in diet-induced glucolipid dysregulation by targeting the gut–liver axis. Its multi-targeted actions on hepatic metabolism, inflammatory signaling, oxidative balance, and gut microbiota composition support its potential as a natural therapeutic agent for metabolic disorders.